A Guide and Tool for Projecting Public Debt and Fiscal Adjustment Paths with Local- and Foreign-Currency Debt - Acosta Ormaechea, Santiago; Martinez, Leonardo (Washington, D.C. : International Monetary Fund, 2021)
This guide presents the analytical underpinnings and a user manual for the Excel-based Public Debt Dynamics Tool (DDT).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Management; Debt; National Government Expenditures and Related Policies; Sovereign Debt; Tax Evasion and Avoidance